Fresh Cut: Safe-Handling Practices for Consumers - Amy Simonne (EDIS)
A variety of fruits and vegetables should be part of one’s healthy diet. However, several foodborne illnesses have been traced to fresh produce. Although fresh cut produce are washed and sanitized before marketing, they are not germ free. You can take steps to reduce your own risk of foodborne illness from fresh produce. This publication is FCS8740, one of a series of the Department of Family, Youth and Community Sciences, Florida Cooperative Extension Service, IFAS, University of Florida. Publication: October 2002.